Reproductive character displacement: insights from genital morphometrics in damselfly hybrid zones - Ballén-Guapacha, Andrea Viviana; Ospina-Garcés, Sandra Milena; Guevara, Roger; Sánchez-Guillén, Rosa Ana (Heredity, 2024)
Reproductive Character Displacement (RCD) refers to the phenomenon of greater differences in reproductive characters between two species when they occur in sympatry compared to when they occur in allopatry to prevent maladaptive hybridization. We explored whether reinforcement of a mechanical barrier involved in the first contact point between male and female genital traits during copulation in the cross between Ischnura graellsii males and Ischnura elegans females has led to RCD, and whether it supports the lock-and-key hypothesis of genital evolution. We employed geometric morphometrics to analyze the shape and size of male and female genital traits, controlling for environmental and geographic factors. Consistent with an increase in mechanical isolation via reinforcement, we detected larger divergence in genital traits between the species in sympatry than in allopatry, and also stronger signal in females than in males. In the Northwest (NW) hybrid zone, we detected RCD in I. graellsii males and I. elegans females, while in the Northcentral (NC) hybrid zone we detected RCD only in I. elegans females and I. elegans males. The detection of RCD in both sexes of I. elegans was consistent with the lock-and-key hypothesis of genital evolution via female choice for conspecific males in this species. Our study highlights the importance of using geometric morphometrics to deal with the complexity of female reproductive structures while controlling for environmental and geographic factors to investigate RCD. This study contributes valuable insights into the dynamics of reproductive isolation mechanisms and genital coevolution.